SELECTED PROGNOSTIC FACTORS OF LONG-TERM RENAL GRAFT FUNCTION - Krejci, Karel (Biomedical papers, 1999)
Kidney transplantation is a method of choice as a treatement for end-stage renal disease in indicated cases.However, the long graft survival represents only about 50% due to various types of rejection as a leading cause ofgraft loss in renal transplant recipients.The early dg. of rejection and especially acute rejection, it's adequatemanagement, decreased risk for the future chronic rejection nefropathy. This is a primary goal of the cliniciancaring for these patients. We use several methods in order to make diagnosis of acute rejection.Urine cytology andurine flow cytometry have been found highly sensitive specific for the early diagnosis of acute rejection, provide ususeful information in differentiation from others causes of graft dysfunction.Urine analysis have some advantageover other diagnostic methodes and can facilitate the observation of a graft over time.
Keywords: Kidney transplantation / Acute graft rejection / Urine analysis